The Transformation of Kafaah Maliyyah into a Socio Legal Principle of Marital Compatibility in Rempoa’s Betawi Community - Abdulloh Abdulloh; Mustori Mustori; Muhammad Hafiduddin; Sugeng Priyono; Rosee Laehseng (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Research on kafaah has so far focused more on the doctrinal and normative dimensions, while the transformation of the meaning of kafaah maliyyah in the context of urban Muslim society is still relatively limited to study. This study aims to analyze the transformation of kafaah maliyyah as a sociolegal principle in determining the compatibility of marriage in the Betawi community in Rempoa, South Tangerang, and explain its implications for the formation of Islamic social and family law relations. The research uses qualitative methods with case study design and sociolegal approaches. Data were obtained through semi-structured interviews with five purposively selected informants, limited field observations, and document analysis, then analyzed using thematic coding techniques that integrated the perspectives of Islamic family law, national marriage law, and Pierre Bourdieu's theory of capital. The results showed that the size of kafaah has shifted from similarity of background, ethnicity, family reputation, and environmental proximity to indicators that emphasize job stability, income security, education level, housing ownership, and the ability to maintain urban household life. This transformation strengthens the tendency towards horizontal marriage based on the equivalence of socio-economic status, while increasing the flexibility of acceptance for non-Betawi couples who have moral and economic credibility. This study concludes that kafaah maliyyah has developed into a living sociolegal principle that is adaptive to urban dynamics. These findings make a theoretical contribution through the recontextualization of the concept of kafaah maliyyah and the development of Bourdieu's theory of capital by showing that economic capital functions as a source of social legitimacy, family acceptance, and marriage consent in urban Muslim societies.